1996
DOI: 10.1051/rnd:19960504
|View full text |Cite
|
Sign up to set email alerts
|

A sucrose-DMSO extender for freezing rabbit semen

Abstract: Summary ― The aim of this study was to define a simple extender for freezing rabbit semen from selected males used to inseminate selected does to obtain embryos for an embryo bank. Four experiments were carried out. In the first experiment, freezing extender was defined on the basis of the results of the post-thawing motility rate. Three factors and their interactions were studied: final concentration of dimethyl sulphoxide (DMSO) (1, 1.25, 1.5 and 1.75 M), egg yolk (0% of 10 v/v) and sugar (none, or 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 8 publications
(12 reference statements)
4
29
1
2
Order By: Relevance
“…The post-thaw sperm-quality parameters observed from different extenders used in this study show that when Me 2 SO was used as permeable cryoprotectant, sucrose replacement by egg yolk had no effect in acrosome integrity after freezing, but provided significantly lower postthawing sperm motility and viability. This finding seems to be consistent with those observed by Vicente and Viudes de Castro (1996), who reported a similar sperm motility with or without egg yolk when the extender contained sucrose. The beneficial effects of sugars in the extender on the post-thaw viability of the mammalian sperm have been reported in several studies (Abdelhakeam et al, 1991;Molinia et al, 1994;Vicente and Viudes de Castro, 1996;Woelders et al, 1997;Malo et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The post-thaw sperm-quality parameters observed from different extenders used in this study show that when Me 2 SO was used as permeable cryoprotectant, sucrose replacement by egg yolk had no effect in acrosome integrity after freezing, but provided significantly lower postthawing sperm motility and viability. This finding seems to be consistent with those observed by Vicente and Viudes de Castro (1996), who reported a similar sperm motility with or without egg yolk when the extender contained sucrose. The beneficial effects of sugars in the extender on the post-thaw viability of the mammalian sperm have been reported in several studies (Abdelhakeam et al, 1991;Molinia et al, 1994;Vicente and Viudes de Castro, 1996;Woelders et al, 1997;Malo et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…This finding seems to be consistent with those observed by Vicente and Viudes de Castro (1996), who reported a similar sperm motility with or without egg yolk when the extender contained sucrose. The beneficial effects of sugars in the extender on the post-thaw viability of the mammalian sperm have been reported in several studies (Abdelhakeam et al, 1991;Molinia et al, 1994;Vicente and Viudes de Castro, 1996;Woelders et al, 1997;Malo et al, 2010). Our results demonstrated that the extender with Me 2 SO and sucrose, in addition to significantly improving post-thawing sperm motility and viability, enhanced the reproductive parameters, increasing the implantation sites and the fertility rate at birth, decreasing the implantation losses, and consequently, increasing the TB.…”
Section: Discussionsupporting
confidence: 93%
“…As for the morphological evaluation of sperm, the results observed in the present work were similar to those reported by other authors working with males of the same rabbit line (85% observed by [32]). The percentage of spermatozoa with cytoplasmic droplets was higher than that reported by other authors working with adult males of the same line (11%, [29]) which is probably due to the youth of the animals (since ejaculates from young males frequently have a high percent of sperm with droplets, [33]).…”
Section: Discussionsupporting
confidence: 92%
“…The motility rate observed in this experiment was lower than the motility rate reported by other authors when working with fresh semen (usually higher than 70% of motile sperm [32,34,35]). This could have been due to the high dilution rate used in this work (dilution 1:50) to measure the motility parameters with the CASA system; [36] observed a pronounced reduction in motility parameters from rabbit spermatozoa when seminal plasma had been diluted more than 30 fold.…”
Section: Discussioncontrasting
confidence: 81%
“…Nowadays, semen freezing is not a reliable or repeatable method yet, and results after AI with rabbit frozen semen are still too inconstant to plan a routine utilization of this technique (Vicente et al, 1996;Moce et al, 2003). Only half of the sampled males can produce semen with freezable quality and approximately 50% of females give birth after insemination of thawed semen with a large variability [15%~80%].…”
Section: Germinal Cellsmentioning
confidence: 99%